Anticardiolipin antibodies in patients with multiple sclerosis do not represent a subgroup of patients according to clinical, familial, and biological characteristics. Issue 5 (1st May 2002) - Heinzlef, O; Weill, B; Johanet, C; Sazdovitch, V; Caillat-Zucman, S; Tournier-Lasserve, E; Roullet, E
Abstract : Background: In multiple sclerosis (MS), case control studies have shown that anticardiolipin antibodies (aCL Ab) are more frequent than in the general population and that aCL Ab positivity may be associated with specific clinical characteristics. Objectives: To determine whether patients with MS who are positive for aCL Ab have specific characteristics. Methods: 285 consecutive patients with MS were tested for aCL Ab positivity. Patients also underwent complete autoimmune screening and were systematically evaluated for clinical characteristics and individual or family history of autoimmune disease. Results: aCL Ab positivity was found in 42 patients (15%). The main isotype was aCL IgM (32 patients, 11%). Demographics and clinical characteristics including sex, age at onset, course of the disease, expanded disability status scale score, and progression index were not different between aCL Ab positive and aCL Ab negative patients. Clinical systems involved at onset or during the course of the disease were not different from what is usually observed in MS. aCL Ab positivity was not associated with an increased frequency of autoimmune disease and was not predictive of a family history of autoimmune disease. Patients positive for aCL IgM were more frequently positive for the presence of non-organ specific antibodies (53% v 39%, respectively, p = 0.02). Conclusions: These results do not support the hypothesis that patients with MS with aCL Ab constitute a subgroup of MS according to demographic clinical and familial characteristics. The greater frequency of other antibodies in aCL Ab positive patients suggests that they only reflect a more general autoimmune activation in MS.